Effects of aeration and chemical treatments on nutrient release from the bottom sediment of tropical marine shrimp ponds - Md. Yusoff, Fatimah; Law, Ah Theem; Soon, Janny (Asian Fisheries Society, 2003)
The effects of aeration, and addition of aluminum sulfate (alum) and calcium carbonate on the release of nutrients from shrimp pond bottom sediments to the overlying water were studied in laboratory using sediment-water systems. Soluble reactive phosphorus (SRP) concentrations in the water column showed a decreasing trend culminating with the lowest values after 21 days of experiment, indicating strong adsorption of SRP by the sediment. Aeration significantly (p<0.05) decreased SRP concentrations compared to tanks without aeration in 14 days. During the first seven days, the addition of alum and calcium carbonate significantly (p<0.05) enhanced the decrease of SRP in the water column both in the aerated and unaerated tanks. The addition of alum did not affect the water pH, probably due to high buffering capacity of the marine pond water. From day 14 onwards, SRP concentrations in the aerated alum and calcium carbonate treatments had significantly higher SRP than the unaerated systems, probably due to the positive correlation between P-release and mixing energy, and higher pH and nitrate values in the aerated systems. Total ammonia nitrogen significantly decreased with aeration and the addition of lime. Total ammonia was not detected after day 14 as it was probably oxidized to nitrite and nitrate, adsorbed to the sediment or lost to the atmosphere at high pH. Nitrite concentrations were high in unaerated tanks only during the first 14 days and remained low thereafter. Nitrate remained high throughout the experiment, as there was absence of phytoplankton uptake in the system. This study illustrated that aeration together with the addition of alum and calcium carbonate may help control the release of excessive SRP and ammonia from the pond bottom sediments and minimize the occurrence of eutrophication and water quality deterioration in shrimp ponds.